Representasi Budaya Bali pada Film A Perfect Fit: Analisis Semiotika Roland Barthes - Utami, Aidha Nur (Universitas Ahmad Dahlan, 2024)
A film is a literary work in the form of moving images or videos that can be seen, heard, and shown to convey information or a message to the general public. Films have various ways of depicting various realities of life, including social realities related to daily life, politics, psychology, culture, and others. This research aims to examine films that represent the reality of life in Balinese culture, namely the film A Perfect Fit. The method used in this research is a qualitative descriptive method, with a study of Roland Barthes' semiotic analysis. Data collection techniques were carried out using reading and note-taking techniques. Based on the research results, there are eight pieces of Balinese culture in the film A Perfect Fit, namely Canang Sari, Melukat, Kecak Dance, Balinese Karawitan, Prayer, Traditional Balinese Wedding Clothing, Mepantigan or Mud Wrestling, and Lontar Reading.